Charge Controller for Solar-Wind Hybrid Energy Harvesting System - Yap, Hiong Yang; Kok, Boon Ching (Evolution in Electrical and Electronic Engineering, 2023)
The usage of renewable energy in society is growing broader and diversified day by day as environmental awareness is gradually being raised by the new generations. Moreover, the hybrid way of green energy harvesting has become a new trend with the intent to increase the reliability and quality of energy harvesting which is also expected to decrease the cost in terms of electrical tariff. The main objective of this article is to design and construct a prototype of the portable solar-wind hybrid energy harvesting system which is proposed with an innovative concept of a hybrid charge controller. The charge controller is designed to regulate both sources with different corresponding voltage levels which result in a common desired output voltage level. The maximum regulated output for the current of 6.21A is 13.8 V where the maximum output power is 85.7 W. The most significant limitation of this converter is the acceptance range of input voltage level for regulation is quite narrow after tunned with certain desired output voltage levels. The portability of this system makes it possible to be applied on vehicles and automatic machines as it is capable of supporting small power application devices.